2006
DOI: 10.1128/jb.00873-06
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Genetic Components of Streptomyces lividans Linear Plasmid SLP2 for Replication in Circular and Linear Modes

Abstract: Unlike most eubacteria, Streptomyces species usually contain linear chromosomes and plasmids (9,16,17). The linear plasmids are 12 to 1,700 kb long (16,27). Their telomeres contain inverted repeat sequences from 44 bp (7) to 180 kb (19), and their 5Ј telomeric ends are linked covalently to terminal proteins (1, 28). Unlike linear replicons of adenoviruses and bacteriophage 29, which also contain terminal proteins linking covalently to 5Ј telomeric DNA ends and undergo replication by a mechanism of strand displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 28 publications
(41 reference statements)
0
16
0
Order By: Relevance
“…In the absence of the partitioning, transfer, and spread systems, the plasmid (SLP2tsr⌬par⌬tra⌬spd) was almost completely lost after a sporulation cycle in S. coelicolor. Although we could not create such a triple mutation in SLP2tsr in S. lividans, the mini-SLP2 plasmids created by Xu et al (36), which contained only the basic replication locus of SLP2, were also highly unstable in S. lividans (about 99% loss), supporting the importance of the three systems in SLP2 maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of the partitioning, transfer, and spread systems, the plasmid (SLP2tsr⌬par⌬tra⌬spd) was almost completely lost after a sporulation cycle in S. coelicolor. Although we could not create such a triple mutation in SLP2tsr in S. lividans, the mini-SLP2 plasmids created by Xu et al (36), which contained only the basic replication locus of SLP2, were also highly unstable in S. lividans (about 99% loss), supporting the importance of the three systems in SLP2 maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier work showed that Streptomyces linear plasmids commonly contain one internal origin of replication (6,12,16,32,36,39,42,46). Here, we found that the 54,288-bp pFRL1 contained two internal replication loci, one next to a telomere and another ϳ10 kb from it.…”
Section: Discussionmentioning
confidence: 51%
“…The centrally located replication locus of pSLA2 consists of a rep gene (encoding a DNA helicase) and its adjacent iterons (6). Such rep (helicase and adjacent iterons) loci are also found in pSCL1, SCP1, SLP2, and pSHK1 (16,32,36,40,42,46) while other loci consisting of a rep gene encoding a hypothetical protein and its adjacent noncoding sequence (ncs) have been identified in pSLA2-L, pSCL2, pRL2, pRL4, and pFRL2 (12,39,46). The minimal origin required for maintaining the replication of pSLA2 in the circular mode cannot promote its propagation in the linear mode unless it also contains an rlrA gene.…”
mentioning
confidence: 99%
“…In the case of the linear plasmid SLP2, efficient replication as a circular derivative requires a 47 bp sequence upstream of 23-mer iterons. Inclusion of these sequences increased the transformation efficiency by about 1000 fold (41). This region is not transcribed as shown by RT PCR and hence may contain regulatory factor(s) that act in cis (41).…”
Section: Replication Of Linear Plasmidsmentioning
confidence: 99%
“…Inclusion of these sequences increased the transformation efficiency by about 1000 fold (41). This region is not transcribed as shown by RT PCR and hence may contain regulatory factor(s) that act in cis (41). SLP2 contains two tpg homologues -tpg SLP2 and a putative pseudogene on the right arm.…”
Section: Replication Of Linear Plasmidsmentioning
confidence: 99%